Inference of Intercellular Communications and Multilayer Gene-Regulations of Epithelial–Mesenchymal Transition From Single-Cell Transcriptomic Data - Sha, Yutong; Wang, Shuxiong; Bocci, Federico; Zhou, Peijie; Nie, Qing (Frontiers in Genetics, 2021)
Epithelial to mesenchymal transition (EMT) plays an important role in many biological processes during development and cancer. The advent of single-cell transcriptome sequencing techniques allows the dissection of dynamical details underlying EMT with unprecedented resolution. Despite several single-cell data analysis on EMT, how cell communicates and regulates dynamics along the EMT trajectory remains elusive. Using single-cell transcriptomic datasets, here we infer the cell-cell communications and the multilayer gene-gene regulation networks to analyze and visualize the complex cellular crosstalk and the underlying gene regulatory dynamics along EMT. Combining with trajectory analysis, our approach reveals the existence of multiple intermediate cell states (ICS) with hybrid epithelial and mesenchymal features. Analysis on the time-series datasets from cancer cell lines with different inducing factors show that the induced EMT are context-specific: the EMT induced by TGFB1 is synchronous while the EMT induced by EGF and TNF are asynchronous, and the response of TGF-β pathway in terms of gene expression regulations are heterogeneous under different treatments or among various cell states. Meanwhile, network topology analysis suggests that the ICS during EMT serve as the signaling in cellular communication under different conditions. Interestingly, our analysis of a mouse skin squamous cell carcinoma (SCC) dataset also suggests regardless of the significant discrepancy in concrete genes between in-vitro and in-vivo EMT systems, the ICS play dominant role in the TGF-β signaling crosstalk. Overall, our approach reveals the multiscale mechanisms coupling cell-cell communications and gene-gene regulations responsible for complex cell-state transitions.